Evaluation of fermented soybean meal sources in diets for nursery pigs - Jeffrey, Andrea M.; Frobose, Hyatt L.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 296 mixed-sex pigs (PIC 327 × 1050; 14.5 ± 3.0 lb BW and 21 d of age) were used in a 31-d experiment evaluating the effect of further processing methods for soybean meal on weanling pig growth performance. There were 11 replicate pens per treatment with 6 or 7 pigs per pen. At weaning, pigs were allotted to pens by initial weight to 1 of 4 treatments in a completely randomized design. Experimental treatments were: (1) negative control (NC: no specialty protein sources), (2) fermented soybean meal processing method 1 (FSBM 1), (3) fermented soybean meal processing method 2 (FSBM 2), and (4) enzymatically treated soybean meal (ETS). The specialty soybean meal protein sources were included in Phase 1 (d 0 to 7) and Phase 2 (d 7 to 20) diets at 5%, and diets were formulated to the same standardized ileal digestible (SID) amino acid level. All pigs were subsequently fed a common diet during Phase 3 (d 20 to 31). Phase 1 and 2 diets were fed in pellet form, whereas the Phase 3 common diet was fed in meal form. Nutrient analyses of specialty soybean meal ingredients were conducted and generally matched those used for diet formulation. From d 0 to 7, pigs fed FSBM 2 had increased (P < 0.05) ADG and BW compared with pigs fed ETS, whereas those fed NC and FSBM 1 were intermediate. No other differences were observed between treatments for growth or BW during the experimental period, common period, or overall. In summary, further processed soybean meal sources did not improve nursery pig growth compared with traditional soybean meal.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Fermented soybean meal; Nursery pig; Protein sources